Answer :

P(AB) = , P = (Given)


Now,


P = P(AB) (1)


P(AB) = 1 - P(AB)


From (Given) & (1)



Also,


P = 1 – P(A) (2)


P = 1 – P(B) (3)


Now, according to the addition theorem of probability:


P(AB) = P(A) + P(B) – P(AB)




From (2) & (3)



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

Fill in theMathematics - Exemplar

A speaks truth inMathematics - Board Papers

Often it is takenMathematics - Board Papers

Assume that each Mathematics - Board Papers

A bag X contains Mathematics - Board Papers